2019
DOI: 10.2139/ssrn.3469995
|View full text |Cite
|
Sign up to set email alerts
|

Buildings' Energy Efficiency and the Probability of Mortgage Default: The Dutch Case

Abstract: In this paper, we investigate the relation between buildings' energy efficiency and the probability of mortgage default. To this end, we construct a novel panel dataset by combining Dutch loan-level mortgage information with provisional building energy ratings that are calculated by the Netherlands Enterprise Agency. By employing the Logistic regression and the extended Cox model, we find that buildings' energy efficiency is associated with lower likelihood of mortgage default. The results hold for a battery o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…The research recognizes a gap in the current literature, where most studies in the banking sector focus on credit risk assessment (Rozo et al, 2023), time to default (Billio et al, 2019), and factors leading to bankruptcy (Grynko et al, 2017;Caselli et al, 2021). This study addresses the lack of research on customer retention, emphasizing the importance of not just recovering funds but encouraging customers to continue using banking services even after their loans are repaid.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…The research recognizes a gap in the current literature, where most studies in the banking sector focus on credit risk assessment (Rozo et al, 2023), time to default (Billio et al, 2019), and factors leading to bankruptcy (Grynko et al, 2017;Caselli et al, 2021). This study addresses the lack of research on customer retention, emphasizing the importance of not just recovering funds but encouraging customers to continue using banking services even after their loans are repaid.…”
Section: Discussionmentioning
confidence: 96%
“…The authors used an Accelerated Failure Time Model. Billio et al (2019) investigate the relationship between building energy efficiency and the probability of mortgage default in the Netherlands using a panel dataset with information on mortgage loans and building energy efficiency ratings. Using logit regression and an extended Cox model, the authors found that building energy efficiency is associated with a lower probability of mortgage default.…”
Section: Literature Reviewmentioning
confidence: 99%